Peningkatan repurchase intention dari peran digital marketing, customer experience, dan customer satisfaction terhadap pelanggan coffee shop di Jakarta - Liando, Victoria Regine; Keni, Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
The growth of coffee consumption in Indonesia has driven the expansion of coffee shops, particularly in Jakarta. Amid intense competition, enhancing customer loyalty has become a strategic priority, especially in increasing repurchase intention. This study aims to analyze the influence of digital marketing, customer experience, and customer satisfaction on repurchase intention among coffee shop customers in Jakarta. A quantitative approach was employed through a survey of 100 active coffee shop customers in Jakarta. The data were analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The results indicate that digital marketing, customer experience, and customer satisfaction have a positive and significant impact on repurchase intention. These findings highlight the importance of adaptive digital strategies, holistic customer experiences, and quality service in ensuring business sustainability.